Doppler changes in umbilical artery and ductus venosus during fetoscopic prenatal surgical repair of myelomeningocele. (28th January 2019) - Kassir, E.; Belfort, M. A.; Shamshirsaz, A. A.; Sanz Cortes, M.; Whitehead, W. E.; Espinoza, J.
ABSTRACT: Objective: Cardiac dysfunction has been described in 60% of fetuses undergoing open myelomeningocele (MMC) repair. Routine Doppler evaluation of the umbilical artery (UA) and ductus venosus (DV) is challenging during fetal surgery. The aim of this study was to describe Doppler changes in the UA and DV in a cohort of fetuses during fetoscopic MMC repair. Methods: This was a retrospective study of fetuses that underwent fetoscopic repair of MMC at a single institution between 2014 and 2017. Ultrasound images taken intraoperatively were analyzed to describe the changes in Doppler parameters of the UA and DV during fetoscopic MMC repair. The timing of Doppler changes was matched with the phase of surgery to determine whether a pattern to their appearance could be ascertained. Results: Of the thirty‐five cases of fetoscopic MMC repair performed during the study period, Doppler data were available for 15. Of these, UA Doppler data were obtained in 12 cases, and DV Doppler data were obtained in 13 cases. Of the 12 cases for which there were UA data, nine (75%) showed transient absence of end‐diastolic flow (EDF), with five (41.7%) of them progressing to reversal of EDF. Of the 13 cases for which there were DV data, nine had elevated pulsatility index; however, none of them had absent or reversed blood flow during atrial contraction. Of the nine cases with absent EDF in the UA, this abnormality first appeared during fetoscopic repair in five (55.6%), after uterus exteriorization but before CO2 insufflation in two (22.2%), after uterus replacement but before skin closure in one (11.1%) and after CO2 insufflation but before the start of the MMC repair in one (11.1%). Doppler abnormalities in four fetuses with reversed EDF and in three with absent EDF resolved during surgery. Follow‐up examination 1 day after surgery demonstrated resolution of UA and DV Doppler abnormalities in all fetuses. Conclusion: Transient Doppler abnormalities of the UA, without significant changes in the DV, can be seen during fetoscopic MMC repair. The clinical significance of these Doppler findings remains unclear due to their transient and intermittent nature. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.